(untitled) (Bangladesh Journal of Nuclear Medicine, 2025)
Positron Emission Tomography-Computed Tomography (PET-CT) is an innovative hybrid imaging technique that effectively combines functional and anatomical imaging. This integration enhances the diagnosis and treatment of a wide range of diseases, proving to be particularly valuable in fields such as oncology, neurology, cardiology, and infectious disease management. By offering detailed insights into disease mechanisms, progression, and responses to therapy, PET-CT plays a crucial role in advancing patient care. The continued development of PET-CT incorporates cutting-edge techniques, including the use of novel radiotracers, hybrid imaging modalities, and artificial intelligence (AI)-based image analysis. This review aims to spotlight the technological advancements, emerging trends, application in research, clinical applications, and challenges associated with PET-CT while emphasizing its potential in personalized medicine and the ongoing integration of novel radiotracers and AI technologies. Despite certain limitations, PET-CT is a vital component of modern medical imaging, significantly contributing to the evolution of precision healthcare. Bangladesh J. Nuclear Med. 28(1): 149-155, 2025